Fe‐Based Complexes as Styrene Aziridination Catalysts: Ligand Substitution Tunes Catalyst Activity. Issue 21 (28th August 2019) - Coin, Guillaume; Patra, Ranjan; Clémancey, Martin; Dubourdeaux, Patrick; Pécaut, Jacques; Lebrun, Colette; Castro, Ludovic; Maldivi, Pascale; Chardon‐Noblat, Sylvie; Latour, Jean‐Marc
Abstract: As part of our effort to improve our understanding of aziridination mechanism, we used tetra substitution of a diphenol ligand to modify the redox properties of corresponding Fe complexes. This allowed us to confirm that aziridination catalysis by Fe‐based complexes is governed by electron affinity of the active species and further show that it correlates with the Fe III /Fe II redox potential. Abstract : Catalyst tuning : Iron aminophenolates: aziridination yields parallel the Fe III/II reduction potentials of the catalyst precursors allowing to evaluate the aziridination capacity of the catalyst by cyclic voltammetry experiments.